2004
DOI: 10.1007/s00439-004-1192-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel ARH splice site mutation in a Mexican kindred with autosomal recessive hypercholesterolemia

Abstract: Autosomal recessive hypercholesterolemia (ARH) is characterized by elevated LDL serum levels, xanthomatosis, and premature coronary artery disease. Three loci have been described for this condition (1p35, 15q25-q26 and 13q). Recently, the responsible gene at the 1p35 locus, encoding an LDL receptor adaptor protein (ARH) has been identified. We studied a Mexican ARH family with two affected siblings. Sequence analysis of the ARH gene (1p35 locus) revealed that the affected siblings are homozygous for a novel mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Xanthomatosis is rarely observed in young children, and when present, homozygous familial hypercholesterolemia (FH) or autosomal recessive hypercholesterolemia is most often suspected 37 38) . Xanthomas may begin to appear at very young age in sitosterolemia, sometimes during the first year of life 33 35) .…”
Section: Clinical Spectrum Of Sitosterolemiamentioning
confidence: 99%
“…Xanthomatosis is rarely observed in young children, and when present, homozygous familial hypercholesterolemia (FH) or autosomal recessive hypercholesterolemia is most often suspected 37 38) . Xanthomas may begin to appear at very young age in sitosterolemia, sometimes during the first year of life 33 35) .…”
Section: Clinical Spectrum Of Sitosterolemiamentioning
confidence: 99%
“…Recently, the mutation (T56M) of ARH has been associated with hypercholesterolemia (33). Thus far, this is the only point mutation identified on the PTB domain of ARH, but no effect on its binding to LDLR could be detected in a pull-down assay (34). We studied the binding of the LDLR peptide by the corresponding rARH mutant (T55M) in comparison with WT rARH by SPR.…”
Section: Hypercholesterolemia-causing Mutations Destabilize the Arh-ldlrmentioning
confidence: 99%
“…Canizales-Quinteros et al (37) reported the characteristics of two Mexican siblings who were found to have a novel splice site mutation at the 1p35 locus (IVS4+2T>G) of the LDLRAP gene. LDLRAP encodes a protein required for clathrin-mediated internalization of the LDLR in the liver.…”
Section: Genetics Of Fh In Latin Americamentioning
confidence: 99%